A Review on the Effect of Sand Dune on the Hydrodynamic Properties of Rivers - Manimaran, Rajaletchumi (Universiti Teknologi PETRONAS, 2020)
Rivers are one of the water sources used by humans for various purposes including irrigation, sand mining, potable water supply, transportation, to carry out leisure activities and production of electricity through hydroelectric dams. However, these uses can impact the river and its surrounding ecosystems. One of the impacts includes the formation of sand dune which can severely affect a river profile. Sand dune changes the surface morphology of a river which eventually might affect the river flow and disrupt the water supply for the various uses mentioned above. Studies should be carried out to understand the effects of sand dune on the hydrodynamic properties of river flow. There are a number of methods used by researchers to study this issue and the common methods include the usage of numerical models and experimental works.